Factors influencing reproductive performance in a range of network situations - Thorpe, W.R.; Coulibaly, L.; Defly, A.; D'Ieteren, G.D.M.; Feron, A.; Grundler, G.; Hecker, P.; Itty, P.; Maehl, J.H.H.; Mawuena, K.; Morkramer, G.; Mulungo, M.; et al. (ILCA/ILRAD, 1988)
Evaluates the effects of trypanosome infection and other factors on parturition interval (1984-1986) at Network sites of Avetonou, Boundiali & Mushie. Presents data on litter size, lambing interval and calving interval.